2001
DOI: 10.1074/jbc.m101585200
|View full text |Cite
|
Sign up to set email alerts
|

Aggretin, a Heterodimeric C-type Lectin from Calloselasma rhodostoma (Malayan Pit Viper), Stimulates Platelets by Binding to α2β1 Integrin and Glycoprotein Ib, Activating Syk and Phospholipase Cγ2, but Does Not Involve the Glycoprotein VI/Fc Receptor γ Chain Collagen Receptor

Abstract: Aggretin, a potent platelet activator, was isolated from Calloselasma rhodostoma venom, and 30-amino acid N-terminal sequences of both subunits were determined. Aggretin belongs to the heterodimeric snake Ctype lectin family and is thought to activate platelets by binding to platelet glycoprotein ␣ 2 ␤ 1 . We now show that binding to glycoprotein (GP) Ib is also required. Aggretin-induced platelet activation was inhibited by a monoclonal antibody to GPIb as well as by antibodies to ␣ 2 ␤ 1 . Binding of both of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 43 publications
3
64
2
Order By: Relevance
“…Many snake C-type lectins that activate platelets to various extents have been reported that either have different receptors or have different affinities for the same receptors, even though they share a high degree of sequence similarities. For example, bilinexin only agglutinates platelets using GPIb and ␣ 2 ␤ 1 as receptors (36), whereas these same glycoproteins are also employed by aggretin to stimulate full platelet activation (25). This may indicate that they have different binding sites for/on each receptor and/or that aggretin may bind to (an) additional receptor(s).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many snake C-type lectins that activate platelets to various extents have been reported that either have different receptors or have different affinities for the same receptors, even though they share a high degree of sequence similarities. For example, bilinexin only agglutinates platelets using GPIb and ␣ 2 ␤ 1 as receptors (36), whereas these same glycoproteins are also employed by aggretin to stimulate full platelet activation (25). This may indicate that they have different binding sites for/on each receptor and/or that aggretin may bind to (an) additional receptor(s).…”
Section: Discussionmentioning
confidence: 99%
“…Echicetin, aggretin, rhodocetin, and convulxin were purified from Echis carinatus sochureki venom (Latoxan, Valence, France), Calloselasma rhodostoma venom (CV Herpafauna, Indonesia), and Crotalus durissus terrificus venom (Sigma), respectively, as described previously (10,25,28,29). Alboaggregin B and alboaggregin A were isolated from Trimeresurus albolabris venom from Huangshang, China, and from Latoxan (Valence, France), respectively (22,30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second C-type lectin with dual affinity for GPIb␣ and GPVI is alboluxin, identified in the venom of Trimeresurus albolabris (7). Another example of the promiscuity of C-type lectins might be the behavior of aggretin, derived from Calloselasma rhodostoma (18). Aggretin (rhodocytin) was initially reported to bind to the integrin collagen receptor ␣ 2␤1 (19) and later reported to also bind to GPIb (18).…”
Section: Discussionmentioning
confidence: 99%
“…Another example of the promiscuity of C-type lectins might be the behavior of aggretin, derived from Calloselasma rhodostoma (18). Aggretin (rhodocytin) was initially reported to bind to the integrin collagen receptor ␣ 2␤1 (19) and later reported to also bind to GPIb (18). However, more recent studies with genetically engineered murine platelets that lack ␣ 2␤1 and GPVI and were stripped of GPIb by proteolysis challenge these conclusions, showing that none of these receptors is required for platelet activation by rhodocytin (20).…”
Section: Discussionmentioning
confidence: 99%